The desire to migrate: constructing a theory of migrationfrom multiplicity - Marques Martins, Isis do Mar (Geografares, 2026)
Migration, as part of reality, has highly particular and plural dimensions and viewpoints. If we consider the expectations of migrants themselves, we find one set of interpretations; if we examine it through the lens of the state, the media, or society, new perspectives and gazes emerge. This study aims to contribute new interpretations to the field of migration studies, framed first through a geographical lens, second through the perspective of multiplicity, and third through a critical social theory of the desire to migrate. Here, the desire to migrate is approached as an inherently political construct that drives strategies of both mobility and permanence. Thus, through a spatial perspective, this paper seeks to understand and advance the debate within the geographies of migration, overcoming traditional theoretical and methodological limitations.